METHODOLOGY FOR TEACHING SAMPLES OF FOLK ORAL CREATIVITY IN ELEMENTARY SCHOOL NATIVE LANGUAGE AND READING LITERACY CLASSES - Hayitboeva Umida Nishanboy daughter (American Journals, 2023)
In this article, the methodology for teaching samples of folk oral creativity in primary class mother tongue and reading literacy classes, folk oral creativity, etiquette, ethics, moral education, upbringing, self-education upbringing.
Keywords: Oral, creativity, cultures, art, fairy tale, courage.